Comparison of de novo versus upgrade cardiac resynchronisation therapy on clinical effect and long-term outcome. Issue 9 (19th November 2021) - Stassen, Jan; Scherrenberg, Martijn; Dilling-Boer, Dagmara; Vijgen, Johan; Koopman, Pieter; Schurmans, Joris; Herbots, Lieven; Verwerft, Jan; Schroyens, Matthew; Timmermans, Philippe
Abstract: Background: The benefit of de novo cardiac resynchronisation therapy (CRT) implantation in selected patients with heart failure is well known. The number of upgrade procedures is increasing but data on clinical response and outcome are less well documented as compared to de novo implantation. Objectives: To investigate the efficacy and outcome of CRT upgrade procedures in patients with existing cardiac implantable electronic devices (CIEDs). Methods: Baseline characteristics, change in New York Heart Association (NYHA) functional class, echocardiographic parameters, life-threatening ventricular tachyarrhythmias, all-cause mortality and mode of death were evaluated in CRT patients with the comparison between de novo and upgrade CRT procedures. Results: About 410 patients (CRT upgrade/ de novo CRT, n  = 97/313) were followed for 63.5 ± 38.1 months. Upgrade patients were older (75.5 ± 8.1 vs 69.9 ± 10.7 years; p  < 0.001), had more often an ischaemic cause of heart failure (58.8% vs 45.4%; p  = 0.021), a higher NYHA functional class ( p  = 0.004) and a higher comorbidity burden. Improvement in left ventricular ejection fraction (LVEF) was higher in the de novo CRT group (8.4 ± 9.9 vs 11.0 ± 10.3%; p  = 0.035). Clinical response was similar between both groups (60.5 vs 62.5%; p  = 0.793), as was mortality at 1 year (8.2 vs 5.8%; p  = 0.351) and at last follow-up (33.0 vs 28.8%; p  = 0.447). The proportion of cardiovascular related deaths was similar between both groups (46.9% vs 38.9%; p  = 0.531). Conclusions: Patients with CRT upgrade procedures have similar symptomatic improvements, as well as 1 year and long-term outcome as compared to patients with de novo CRT implantation.